The relationship between self-stigma and quality of life in long-term hospitalized patients with schizophrenia: a cross-sectional study - Liu, Fuquan; Deng, Hu; Hu, Na; Huang, Wenqian; Wang, Hong; Liu, Lin; Chai, Jiabao; Li, Ying (Frontiers in Psychiatry, 2024)
Objective: To investigate self-stigma's influence on schizophrenia patients' quality of life and its mediated impact by various factors. Methods: This study adopted a cross-sectional design and randomly selected 170 hospitalized patients with schizophrenia for evaluation. The assessment tools included the Positive and Negative Syndrome Scale (PANSS), Internalized Stigma of Mental Illness Scale (ISMI), Schizophrenia Quality of Life Scale (SQLS), and Coping Questionnaire for Schizophrenia Patients (CQSP), among others. Correlation analysis, regression analysis, and mediation analysis were used to test the correlation and mediation effects. Results: Self-stigma had a significant impact on quality of life (T = 8.13, p = 0.00). When self-stigma is used as a mediator, the problem-solving factor in coping strategies has an indirect effect on quality of life, which is significant (AB = -0.16, P = 0.02), while the avoidance factor in coping strategies has a direct effect on quality of life, which is significant (C' = 0.54, p < 0.001), and an indirect effect, which is also significant (AB = 0.25, p < 0.001). Conclusion: The study highlights the significant impact of selfstigma on the quality of life of schizophrenia patients, emphasizing the crucial roles of self-esteem and coping strategies. These findings suggest clinical interventions to improve quality of life should focus on reducing self-stigma, especially enhancing self-esteem and promoting adaptive coping strategies. By addressing these factors, we can better support the mental health and well-being of those with schizophrenia, offering an effective approach to rehabilitation.